Megtört a csend Bács-Kiskun megyében és Kecskeméten - 1988 - Falusi Norbert (Középkori és Kora Újkori Magyar Történeti Tanszék Szeged, 2023)
There was no open, pluralistic, democratic social public sphere in the one-party system of the socialist Hungary. The events of 1988–1989 were classified in different ways, but from our point of view, the framework for interpretation is the crisis of the communist system. In the Soviet model, alternative policy responses disappeared for nearly four decades. The situation changed in 1988, when more and more new social organisations started to claim a role in the political discourse. In addition to the new knowledge and the new perspectives, important results of fundamental research focus on the local and regional level that allows a more detailed description and understanding of the transition from the socialist to the capitalist social system.
Keywords: Bölcsészettudományok; Történettudomány és régészet